Long-term outcome of knee and ankle injuries in elite football - Larsen, E.; Jensen, P. K.; Jensen, P. R. (Scandinavian Journal of Medicine & Science in Sports, 1999)
To estimate the risk and evaluate the long-term outcome of knee and ankle injuries in former national team elite football, 69 players were randomly selected, followed by clinical and stress radiographic examinations. Thirty-nine players (49 knees) had had knee injuries and 29 ankle injuries (35 ankles). The median time from injury until study examination was 25 years. The knee injuries were tears of the medial collateral ligament (MCL) in 24 cases combined with rupture of the anterior cruciate ligament (ACL) and meniscus lesions in three. Meniscus lesions had occurred in 17 cases including three combined with ACL and MCL and another two with ACL ruptures. Isolated rupture of the ACL had occurred in four cases. The ankle lesions were in 26 of 35 cases ruptures of the lateral ligaments. In all, 12 players had completely stopped football and three had changed occupation. Signs of arthritis were present in 63% of the injured knees and in 33% of the injured ankles. The incidence of arthritis in the group of 17 uninjured players was 26% in the knee and 18% the ankle. In elite football players knee and ankle injuries seem to have a serious long-term outcome, but also uninjured players have a higher risk of developing arthritis than the normal population. Scand J Med Sci Sports 1999 Oct;9(5):285-9